2015
DOI: 10.4172/2157-7471.1000296
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Diversity in Rhizoctonia Solani Causing Sheath Blight in RicePathogenicitya

Abstract: Knowledge of variations in Rhizoctonia Solani causing rice sheath blight disease in different geographic regionsis still scarce and may be a useful tool for examining the nature and spread of population, disease epidemiology and host-pathogen interaction within rice patho-system. Molecular markers provide a basis for identifying patterns, dispersal and colonization in spatial and temporal distribution of pathogenic population and in development of species concepts by providing information about the limits of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…isolate UGM-RBAF had perpendicular hyphae with a septum, a white colony that change to brownish-white when old, light brown to dark brown sclerotium with a round shape (diameter of 1.33-1.58 mm, the weight of 0.17 g/ Petri dish, and amount of 19.5/petri), and a growth rate of 40 mm/day (Figure 1d-f). The characteristics of R. solani isolate UGM-RBAF were similar to R. solani characterized by R. Singh et al (2015). Budiarti et al (2020) reported that 41 R. solani isolates isolated × 100 (C -T) C I = from Indonesia had cultural and morphological characteristics, i.e.…”
Section: Resultsmentioning
confidence: 58%
“…isolate UGM-RBAF had perpendicular hyphae with a septum, a white colony that change to brownish-white when old, light brown to dark brown sclerotium with a round shape (diameter of 1.33-1.58 mm, the weight of 0.17 g/ Petri dish, and amount of 19.5/petri), and a growth rate of 40 mm/day (Figure 1d-f). The characteristics of R. solani isolate UGM-RBAF were similar to R. solani characterized by R. Singh et al (2015). Budiarti et al (2020) reported that 41 R. solani isolates isolated × 100 (C -T) C I = from Indonesia had cultural and morphological characteristics, i.e.…”
Section: Resultsmentioning
confidence: 58%
“…The isolate RS4 was found to be highly virulent with 78% disease incidence, while RS1 showed only 9.21% disease incidence. Many workers have reported morphological as well as pathological variations in fungal isolates associated with sheath diseases of rice (Guleria et al, 2007;Singh et al, 2015;Ramos-Molina and Chavarro-Mesa, 2016;Singh et al, 2018). Macro-sized sclerotia forming isolate RS4 was observed to be more virulent than isolate RS3 which formed micro-sized sclerotia; and nonsclerotia forming isolate RS1 was the least virulent.…”
Section: Test For Pathogenicity Of Different Isolatesmentioning
confidence: 99%
“…Such findings emphasize the use of molecular markers for studying fungal pathogens of rice sheath disease. Several studies on rice sheath blight have used molecular markers such as RAPD (Guleria et al, 2007;Susheela, 2012;Lal et al, 2014;Singh et al, 2015), RFLP (Linde et al, 2005), AFLP (Taheri et al, 2007) and ISSR (Guleria et al, 2007;Yugander et al, 2015;Goswami et al, 2017) along with morphological markers. Recently, rDNA-ITS sequencing has been used for identifying variations (Ramos-Molina and Chavarro-Mesa, 2016;Bintang et al, 2017;Singh et al, 2018).…”
mentioning
confidence: 99%